Using ITERS-R in assessing ECCE quality environment: a case study at two selected child care centres in Kuala Lumpur, Malaysia - Badzis, Mastura; Adnan, Nun Amirah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: The increasing reliance on non-familial early childhood care in urban Malaysia has raised concerns regarding the quality of infant-toddler learning environments. Although policy developments have taken place, there remains a lack of standardized assessment tools to evaluate environmental quality in Early Childhood Care and Education (ECCE) centres. Aim : This study aims to address this critical gap by evaluating the quality of two childcare centres in Kuala Lumpur using the Infant Toddler Environment Rating Scale-Revised (ITERS-R). Method : This research employed a qualitative case study design, with data gathered through structured observations and semi-structured interviews to assess both structural and process quality aspects. Result : The findings revealed that both centres provided only minimal to moderate levels of quality, with Nursery A achieving a mean score of 3.52 and Nursery B scoring 2.86. Notable strengths included language interactions and spatial arrangements. However, significant shortcomings were identified in hygiene practices, caregiver consistency, and inclusivity. Conclusion : These results underscore the importance of adapting and contextualizing international instruments such as the ITERS-R to align with Malaysia’s cultural and regulatory frameworks. The study contributes localized insights that can inform quality improvement initiatives in urban ECCE settings throughout the country.